POPULAR CULTURE IN CROSS-CULTURAL COMMUNICATION - Nafisah, Durrotun (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2024)
At present, digital media plays an important role as one of the main sources of information and can also introduce new things to the surrounding environment. In this context, digital media acts as the main tool for disseminating popular culture and also functions as a medium for introducing popular culture to the wider community. communication involving both verbal and non-verbal expressions that include intercultural or cross-cultural aspects. The rapid progress of the era, coupled with the wave of modernization that is difficult to stop, and the shift in lifestyle from traditional to urban lifestyle, have affected all aspects of life by this modernization process. This factor is one of the causes of the emergence of popular culture. From one of these phenomena, the author wants to know how popular culture is viewed from the perspective of cross-cultural communication. The results of this study indicate that popular culture can influence cross-cultural communication at this time, and the media has an important role in the development of popular culture. So with this it is certainly important to understand how messages and information conveyed and received can be sorted by each individual with a background of different cultures in order to minimize conflict in cross-cultural communication. Keywords: Popular Culture, Cross-Cultural Communication, Media.